The effect of heat treatment on the antioxidant activity of sour cherry jams - Pál, Anna; Keczkó, Péter; Sipos, Péter (Acta Agraria Debreceniensis, 2025)
Sour cherry (Prunus cerasus) is a valuable fruit known for its high antioxidant content. Its bioactive substances contribute to health maintenance, as they have strong anti-inflammatory and free radical scavenging properties. Jams made from sour cherries provide a concentrated form of the antioxidant content of fruit, thus can play an important role in a balanced diet. Heat treatment is an essential part of the jam-making process, as it ensures the microbiological stability and longer shelf life of the product. At the same time, heat can significantly affect the antioxidant content of the fruit. In this study, the authors compared the antioxidant content of six different sour cherry jams. Based on the obtained results, it was concluded that the fruit content of sour cherry jams alone is not sufficient to estimate their antioxidant capacity, but the extent of the effect of heat treatment on it is generally independent of the nature of the products. This result highlights that the fruit content and the applied technology play an important role in preserving the antioxidant content of fruits during product processing.